'Going institutional' to overcome obstruction: Explaining the suppression of minority rights in Western European parliaments, 1945−2010. (5th February 2020) - SIEBERER, ULRICH; DUTKOWSKI, JULIA F.; MEIßNER, PETER; MÜLLER, WOLFGANG C.
Abstract: When and why do parliamentary majorities in Europe suppress parliamentary minority rights? This article argues that such reforms are driven by substantive policy conflict in interaction with existing minority rights. Government parties curb minority rights if they fear minority obstruction due to increased policy conflict and a minority‐friendly institutional status quo . Empirical support is found for this claim using comparative data on all reforms in 13 Western European parliaments since 1945. A curbing of minority rights is significantly more likely under conditions of heightened policy conflict and these effects are stronger the more the institutional status quo favours opposition parties. Contrary to frequent claims of consensual rule changes from single‐country studies in Europe, these findings demonstrate the importance of competitive strategies in explaining institutional reform in European parliaments. The conditional impact of the status quo provides interesting theoretical links to historical institutionalist arguments on path dependence.